PENERAPAN NILAI-NILAI PANCASILA DALAM KEHIDUPAN BERMASYARAKAT (Application of pancasila value in community life) - Isma Jati Ruhmani; Zaskia Khaerunisa (Sindoro: Cendikia Pendidikan, 2025)
The word pancasila which comes from Sanskrit which has the meaning of panca, namely five and sila is the basis so it can be interpreted as five joint stones or can also be interpreted with five good behaviors. Understanding the values contained in Pancasila is something that needs to be done by the people of Indonesia. Understanding the values contained in Pancasila is something that needs to be done by the people of Indonesia. Not only by understanding, but as previously expressed, these values must also be practiced in the life of the nation and state. That way, the goal of the nation's life can be achieved. But indonesian people do not fully understand the values of community, nation, and state. That way, the goal of the nation's life can be achieved. But indonesian people do not fully understand the values of community, nation, and state life formulated through Pancasila which is used as the basis of the state, outlook on life, and national ideology in achieving the goals of the Indonesian nation. From the problems that have been explained, this article aims to discuss the application of Pancasila values in community, nation, and state life. This is useful so that the people of Indonesia understand the meaning of the meaning of the value of Pancasila and its application. So, the people of Indonesia can realize this meaning in everyday life. This research uses qualitative research with qualitative research literature studies is research used to investigate, find, describe, and explain the quality or privilege of social influences that cannot be explained, measured or described through quantitative approaches. Researchers collect data from previous studies that are relevant to the title of the published article.